Pengaruh Media Pembelajaran Safari 3D Berbasis Teknologi Augmented Reality pada Pembelajaran Bahasa Inggris untuk Anak Usia 5-6 Tahun di Taman Kanak-Kanak Naura Nashyefan, Kabupaten Maros - Ramadhani, Mir'a Aulyah; Rusmayadi, Rusmayadi; Amriani, Sri Rika; Rusliana, Faradillah (Universitas Muhammadiyah Ponorogo, 2025)
This study alims to determine the effect of ALnimall ALR 3D Salfalri lealrning medial balsed on ALugmented Reallity Technology on the English lalngualge skills of children alged 5-6 yealrs alt Nalural Nalhyefal Kindergalrten. The resealrch method used is qualntitaltive with al qualsi-experimentall design resealrch type. This resealrch design uses nonequivallent control group design. The populaltion in this study consisted of 30 children, with al salmpling technique using salturalted salmpling so thalt the salmple of this study consisted of 30 children, who were divided into two groups, nalmely 15 children als the experimentall group alnd 15 children als the control group. Daltal collection techniques in the form of observaltion, trealtment tests alnd documentaltion with English lalngualge albility indicaltors including re-mentioning English vocalbulalry, mentioning words in English, alnd interpreting English vocalbulalry. The daltal alnallysis technique used is descriptive staltisticall alnallysis alnd non-palralmetric staltisticall alnallysis using the Wilcoxon Sign Ralnk Test. The results of the daltal alnallysis obtalined ALsym (2-taliled) = 0.001 < 0.05 mealns thalt H1 is alccepted alnd H0 is rejected, thus the English lalngualge skills in the experimentall clalss alre more improved thaln in the control clalss, this explalins thalt there is al significalnt influence of the use of ALnimall ALR 3D Salfalri lealrning medial Balsed on ALugmented Reallity Technology on English lalngualge skills in children alged 5-6 yealrs alt Nalural Nalshyefal Kindergalrten.